Sustainability and governance - Lehman, Cheryl R. (Emerald, 2015)
Giving voice to the marginalized, broadly defined, is the aim of this volume in its examination of social life increasingly marked by global inequality and the extension of market rationalities to all arenas. Revealing the outcome to populations, stakeholders, and the environment when policies resting on narrowly constrained logics are employed, these researchers lead the way in probing accounting's participation in significant struggles of our times. In order to better appreciate the consequences of economic globalization, the works examine contemporary rhetoric, governance, politics, and strategies and the manner in which accounting technologies are integrated. These works maintain that transformation is inevitable and they search for possibilities of change that can be manifested in socially equitable practices and improved social justice by enhancing accountability.
Keywords: Business & Economics -- Accounting -- Financial.; Public finance accounting.; Accounting.; Corporate governance.; Sustainability.; Accounting -- Social aspects.; elektronické knihy; electronic books